If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 17 = 7x + -11 Reorder the terms: 17 = -11 + 7x Solving 17 = -11 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 17 + -7x = -11 + 7x + -7x Combine like terms: 7x + -7x = 0 17 + -7x = -11 + 0 17 + -7x = -11 Add '-17' to each side of the equation. 17 + -17 + -7x = -11 + -17 Combine like terms: 17 + -17 = 0 0 + -7x = -11 + -17 -7x = -11 + -17 Combine like terms: -11 + -17 = -28 -7x = -28 Divide each side by '-7'. x = 4 Simplifying x = 4
| 5(2X-1)=10(3X-3)-15 | | 7m-10=4m+5 | | 39=14m-3 | | 4x(2x-3)=0 | | (2/5)n+6=10 | | 12-(1/3)u=2 | | 1b^2-0.5b-6=0 | | 2x-5+1=7-1 | | (1/2)t+6=-7 | | 6x+3=29 | | 2x-4=18x+4 | | 4b+4=-20 | | 8a^2+40ab+50b^2=0 | | 2x-5+2=7-1 | | 4b+4=20 | | (x+5)*(8x+5)= | | .4-2x=-.5(4x-3) | | -5x-8x=-6-46 | | 25w-3w^2-8=0 | | 15v=75 | | 10a^2+ab-2b^2=0 | | .4-2x=-2x+1.5 | | .4-2x=-2x-1.5 | | x+6x=-5-30 | | -15y=45 | | -6q^2-40q-50=0 | | -15y=44 | | x+9x=-4-86 | | (-x)(-x^5)=x^6 | | 24=6q | | x-9x=-4-86 | | 20b=-460 |